Governing urban economies : innovation and inclusion in Canadian city-regions - Bradford, Neil John, 1957-; Bramwell, Allison (Innovation, creativity, and governance in Canadian city-regions., 2014)
Governing Urban Economies is the first detailed scholarly examination of relations among governmental and community-based actors in Canadian city-regions. Comparing patterns of municipal-community relations and federal-provincial interactions across city-regions, this volume tracks the ways in which urban coalitions tackle complex economic and social challenges. Featuring an inter-disciplinary group of established and up-and-coming scholars, this collection breaks new ground in the Canadian urban politics literature and will appeal to urbanists working in a range of national contexts."--Pub. desc.